Increased postpartum haemorrhage, the possible relation with serotonergic and other psychopharmacological drugs: a matched cohort study - Hanna M. Heller; Anita C. J. Ravelli; Andrea H. L. Bruning; Christianne J. M. de Groot; Fedde Scheele; Maria G. van Pampus; Adriaan Honig (BMC, 2017)
Abstract Background Postpartum haemorrhage is a major obstetric risk worldwide. Therefore risk factors need to be investigated to control for this serious complication. A recent systematic review and meta-analysis revealed that the use of both serotonergic and non-serotonergic antidepressants in pregnancy are associated with a higher risk of postpartum haemorrhage. However, use of antidepressants in pregnancy is often necessary because untreated depression in pregnancy is associated with adverse maternal and neonatal outcome, such as postpartum depression, preterm birth and dysmaturity. Therefore it is of utmost importance to unravel the possible association between postpartum haemorrhage and the use of serotonergic and other psychopharmacological medication during pregnancy. Methods We performed a matched cohort observational study consecutively including all pregnant women using serotonergic medication (n = 578) or other psychopharmacological medication (n = 50) visiting two teaching hospitals in Amsterdam between 2010 and 2014. The incidence of postpartum haemorrhage in women using serotonergic medication or other psychopharmacological medication was compared with the incidence of postpartum haemorrhage in 641,364 pregnant women not using psychiatric medication selected from the database of the Netherlands Perinatal Registry foundation (Perined). Matching took place 1:5 for nine factors, i.e., parity, maternal age, ethnicity, socioeconomic status, macrosomia, gestational duration, history of postpartum haemorrhage, labour induction and hypertensive disorder. Results Postpartum haemorrhage occurred in 9.7% of the women using serotonergic medication. In the matched controls this was 6.6% (p = 0.01). The adjusted odds ratio (aOR) before matching was 1.6 (95% CI 1.2-2.1) and after matching 1.5 (95% CI 1.1-2.1). Among the women using other psychopharmacological medication, the incidence of postpartum haemorrhage before matching was 12.0% versus 6.1% (p = 0.08) with OR 2.1 (95% CI 0.9-4.9), and after matching 12.1% versus 4.4% (p = 0.03) with aOR of 3.3 (95% CI 1.1-9.8). Conclusions Pregnant women using serotonergic medication have an increased risk of postpartum haemorrhage, but this high risk is also seen in pregnant women using other psychopharmacological medication. We suggest that this higher risk of postpartum haemorrhage could not only be explained by serotonin, but also by other mechanisms. An additional explanation could be the underlying psychiatric disorder.